2015
DOI: 10.4251/wjgo.v7.i12.389
|View full text |Cite
|
Sign up to set email alerts
|

Neo-adjuvant chemo(radio)therapy in gastric cancer: Current status and future perspectives

Abstract: In the last 20 years, several clinical trials on neoadjuvant chemotherapy and chemo-radiotherapy as a therapeutic approach for locally advanced gastric cancer have been performed. Even if more data are necessary to define the roles of these approaches, the results of preoperative treatments in the combined treatment of gastric adenocarcinoma are encouraging because this approach has led to a higher rate of curative surgical resection. Owing to the results of most recent randomized phase III studies, neoadjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 65 publications
0
24
0
1
Order By: Relevance
“…This treatment has a strong rationale and many theoretical advantages, such as inducing tumor regression, early treatment of micrometastatic lesions, reducing the risk of R1 resection and peritoneal implantation during operation, and assessment of tumor chemosensitivity in vivo . Numerous studies investigated the role of neoadjuvant therapy in solid malignant tumor, with some impressive and encouraging results .…”
Section: Introductionmentioning
confidence: 99%
“…This treatment has a strong rationale and many theoretical advantages, such as inducing tumor regression, early treatment of micrometastatic lesions, reducing the risk of R1 resection and peritoneal implantation during operation, and assessment of tumor chemosensitivity in vivo . Numerous studies investigated the role of neoadjuvant therapy in solid malignant tumor, with some impressive and encouraging results .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that perioperative radio-chemotherapy or chemotherapy regimens had more favorable effects on increasing curative resection rates, disease-free survival, and overall survival ( 3 - 9 ). As a result, the standard treatment for patients with locally advanced gastric cancer no longer relies on surgery alone but also on perioperative radio-chemotherapy or chemotherapy since the 2000s ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… 5 Many studies have indicated that surgery combined with adjuvant chemoradiotherapy could improve patients’ survival with early detection and treatment advances. 6 9 …”
Section: Introductionmentioning
confidence: 99%